2023
DOI: 10.1007/s00705-023-05851-1
|View full text |Cite
|
Sign up to set email alerts
|

Turnip yellows virus variants differ in host range, transmissibility, and virulence

Abstract: Turnip yellows virus (TuYV; family Solemoviridae, genus Polerovirus, species Turnip yellows virus) is a genetically diverse virus that infects a broad range of plant species across the world. Due to its global economic signi cance, most attention has been given to the impact of TuYV on canola (syn. oilseed rape; Brassica napus). In Australia, a major canola exporting country, TuYV isolates are highly diverse with most variation concentrated in open reading frame 5 (ORF 5) which encodes the readthrough domain (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As faba bean production expands, there has been an increase in the detection of pathogenic viruses ( Jones, 2021 ). Currently, over 50 viruses are known to infect faba bean worldwide ( Fresno et al, 1997 ; Babin et al, 2000 ; Bellardi and Rubies-Autonell, 2001 ; Abraham et al, 2010 ; Nakahara et al, 2011 ; Makkouk et al, 2012 ; Kaur et al, 2013 ; Martin et al, 2014 ; Worrall et al, 2015 ; Kraberger et al, 2018 ; Congdon et al, 2023 ), more than 20 of which have been reported in China ( Meng et al, 2022 ). These viruses mainly cause symptoms such as chlorosis, etiolation, necrosis, mosaic, mottling, leaf curl, and dwarfism.…”
Section: Introductionmentioning
confidence: 99%
“…As faba bean production expands, there has been an increase in the detection of pathogenic viruses ( Jones, 2021 ). Currently, over 50 viruses are known to infect faba bean worldwide ( Fresno et al, 1997 ; Babin et al, 2000 ; Bellardi and Rubies-Autonell, 2001 ; Abraham et al, 2010 ; Nakahara et al, 2011 ; Makkouk et al, 2012 ; Kaur et al, 2013 ; Martin et al, 2014 ; Worrall et al, 2015 ; Kraberger et al, 2018 ; Congdon et al, 2023 ), more than 20 of which have been reported in China ( Meng et al, 2022 ). These viruses mainly cause symptoms such as chlorosis, etiolation, necrosis, mosaic, mottling, leaf curl, and dwarfism.…”
Section: Introductionmentioning
confidence: 99%
“…As faba bean production expands, there has been an increase in the detection of pathogenic viruses (Jones, 2021). Currently, over 50 viruses are known to infect faba bean worldwide (Fresno et al, 1997;Babin et al, 2000;Bellardi and Rubies-Autonell, 2001;Abraham et al, 2010;Nakahara et al, 2011;Makkouk et al, 2012;Kaur et al, 2013;Martin et al, 2014;Worrall et al, 2015;Kraberger et al, 2018;Congdon et al, 2023), more than 20 of which have been reported in China (Meng et al, 2022). These viruses mainly cause symptoms such as chlorosis, etiolation, necrosis, mosaic, mottling, leaf curl, and dwarfism.…”
Section: Introductionmentioning
confidence: 99%